Effectiveness of Syndromic STI Case Management/RH Training in Knowledge and Practice of Auxiliary Health Workers - Adhikari, C; Sherchan, L; Thapa, SB; Adhikari, LM (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Auxiliary Health Workers (AHWs) are the undergraduate 2nd  class health workforce of Nepal. Syndromic Sexually Transmitted Infection Case Management/Reproductive Health (SSCM/RH) training for AHWs is designed to develop knowledge, attitude and skills. The purpose of this study was to examine the effectiveness of the training in knowledge and practice of AHWs. MATERIAL AND METHODS: Achham district from where all AHWs were purposively selected for cross-sectional study. Total number of trained AHWs was 35 and untrained was 19, who were interviewed to fulfill the structured pretested questionnaire that included knowledge inventory and self reported practice.The data collected from29th May to 25th July, 2005. Written consent was taken from respondents after permission taken from Achham DHO. Statistical tests used were mean, median, SD, Mann-Whitney U test, Spearman's rho and chi-square. Values with p < 0.05 was considered significant. RESULTS : All AHWs were male, with mean age of 32.1 years. Regarding knowledge, the scores in all syndromes diagnosis and treatment regimen were significantly different in two groups except in two syndromes. Two practices were found significant. The median knowledge score was 20 (IQR, 16-22) and 16 (IQR, 12-20) in trained and untrained respectively. Similarly, median practice score was found 14 (IQR, 10-16) and 7 (IQR, 6-9) in trained and untrained respectively. In aggregate, both the practice score (U=38.5, p